2008
DOI: 10.1007/s12149-007-0121-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of 99mTc-HMPAO SPECT in Fahr’s disease

Abstract: Fahr's disease is a rare neurodegenerative syndrome, characterized by massive symmetrical intracerebral calcifications of the basal ganglia, dentate nuclei of the cerebellum, and the adjacent parenchyma. Computerized tomography (CT) is considerably more sensitive to detect these intracranial calcifications than other imaging modalities. The clinical, CT scan, and 99(m)Tc-D,L-hexamethylpropylene amine oxime (99(m)Tc-HMPAO) brain perfusion single-photon emission computerized tomography (SPECT) findings in a 42-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
3
0
1
Order By: Relevance
“…1,2,[13][14][15] Several studies of DNTC and Fahr's disease have suggested that neuronal degeneration and calcification occur independently, because regional CBF or metabolism was normal in portions with severe calcification including the basal ganglia and cerebellum. 6,7,11 In addition, similar findings have been reported in autopsy cases, with no apparent degeneration or neuron loss observed in the basal ganglia and cerebellum, despite distinct calcification in those areas. 14,16 Therefore, the CBF asymmetry noted in our case appears to be independent of neuronal degeneration associated with DNTC.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…1,2,[13][14][15] Several studies of DNTC and Fahr's disease have suggested that neuronal degeneration and calcification occur independently, because regional CBF or metabolism was normal in portions with severe calcification including the basal ganglia and cerebellum. 6,7,11 In addition, similar findings have been reported in autopsy cases, with no apparent degeneration or neuron loss observed in the basal ganglia and cerebellum, despite distinct calcification in those areas. 14,16 Therefore, the CBF asymmetry noted in our case appears to be independent of neuronal degeneration associated with DNTC.…”
Section: Discussionsupporting
confidence: 84%
“…Neuropathological changes of DNTC include neurofibrillary tangles, calcareous deposits, glial fibrillary tangles, and vascular changes . Several studies of DNTC and Fahr's disease have suggested that neuronal degeneration and calcification occur independently, because regional CBF or metabolism was normal in portions with severe calcification including the basal ganglia and cerebellum . In addition, similar findings have been reported in autopsy cases, with no apparent degeneration or neuron loss observed in the basal ganglia and cerebellum, despite distinct calcification in those areas .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The usefulness of 99 m Tc-HMPAO brain perfusion SPECT in deciding clinical approach to Fahr's syndrome has been suggested. 12 The treatment of Fahr's syndrome is directed to the identifiable cause especially hypoparathyroidism. In other cases, symptomatic or conservative therapy with clinical follow-up is the rule.…”
Section: Discussionmentioning
confidence: 99%
“…As regards secondary forms, the diagnosis is made, independently of the presence of symptoms, when cerebral calcifications are present at brain imaging, and a specific factor able to cause them is demonstrated. Among the neuroradiologic exams, brain CT is more sensitive than traditional MRI in the detection of calcium deposits [52], but the recently introduced SWI (Susceptibility-weighted imaging) MRI seems to be more sensitive for early changes [53, 54]; another useful tool is the 99mTehexamethyl-propylenamine oxime (99mTc-HMPAO) single proton emission computed tomography (SPECT)[55], revealing markedly decreased perfusion involving the basal ganglia bilaterally and cerebral cortices [56]. …”
Section: Revision Of Literaturementioning
confidence: 99%